Jhum cultivation: The way of livelihood security for Mizoram - Soni, Jeetendra Kumar; Hota, Surabhi; Shakuntala, Ingudam (Indian Farming, 2020)
Jhum or slash and burn cultivation, a form of traditional land-use practice carried out on the slopes of a hill, is known as shifting cultivation due to periodical changing of land rather than changing of crop. Mizoram is the extreme east part of India, in which jhum system of cultivation is the major method of cultivation. It is the way of life which provides subsistence to the dependent community in the form of food, fuel wood and fodder. This system is cyclic in nature and closely associated with the ecological, economical and cultural values of the local people. Jhum cultivation mainly involves selection and removal of forests by slash and burn techniques followed by mixed cropping, harvesting, and fallowing for a short period before abandoning the site. During the fallow period, trees replenish the soil organic matter and above ground vegetation, thereby improving soil structure and prevent soil erosion and excessive water runoff. Thus, ideally, Jhum cultivation is ecologically stable at a very low density of human population and can be operated successfully for subsistence.